Swot-informed english teaching strategies to address mother tongue dominance and build global competence - Pina Dewi Apiyanti; Emay Mastiani (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to explore English learning strategies based on SWOT analysis integrated with the PDSA (Plan-Do-Study-Act) quality management cycle in the context of non-formal education at PKBM Askara Bandung and PKBM Insan Muwahid Garut. The research uses a qualitative approach with case study design and data collection through in-depth interviews, observations, and documentation. The results of the study show that the two PKBMs apply different but complementary adaptive strategies. PKBM Askara emphasizes global competency development through the English Club, adaptive lesson plans based on the Independent Curriculum, and bilingual projects, while PKBM Insan Muwahid focuses on basic communicative skills with the use of simple media. The translanguaging approach is applied as a bridge between the mother tongue and English to facilitate students' understanding. Evaluation is carried out through a combination of tests, observations, projects, portfolios, and reflections, followed by follow-up in the form of program strengthening, remedial, alumni mentoring, and collaborative strategy development. Despite obstacles such as limited resources, mother tongue dominance, diverse student motivations, and varying tutor competencies, SWOT-PDSA integration has proven effective in improving the quality of contextual and globally oriented learning. The findings of this study confirm that SWOT analysis is not only an internal-external mapping tool, but also a strategic framework for planning, implementation, evaluation, and continuous improvement in non-formal education, so that learners are better prepared to face the global challenges of the 21st century.